Evaluation of the association between decreased skeletal muscle mass and extubation failure after long-term mechanical ventilation. Issue 9 (September 2020) - Woo, Hye Young; Oh, Seung-Young; Lee, Hannah; Ryu, Ho Geol
Summary: Background & aims: Elderly patients are being increasingly admitted to the intensive care unit (ICU) for mechanical ventilation (MV) and prevalence of decreased skeletal muscle mass which develop with aging is subsequently increasing. The objective of this study was to identify the association between decreased skeletal muscle mass and extubation failure in patients undergoing long-term MV. Methods: Adults (≥18 years of age) with long-term MV for > 7 days between January 2014 and February 2019 were included retrospectively. Patients who died or were transferred with MV, underwent tracheostomy with failure of weaning from MV, and had not undergone abdominal computed tomography within 3 days before or after intubation were excluded. Failed extubation was defined as reintubation within 48 h after extubation following long-term MV for >7 days. We divided the patients into extubation success and failure groups. Results: Parameters including patients' demographics, cause of intubation, initial setting of MV, maximum inspiratory pressure (MIP) and rapid shallow breath index (RSBI) at extubation, and skeletal muscle mass were compared between the two groups. Decreased skeletal muscle mass was set a standard as a L3 muscle index of less than 49 cm 2 /m 2 for men and of less than 31 cm 2 /m 2 for women using Korean-specific cut-offs for sarcopenia as evaluated on previous epidemiologic study. Among 104 patients who were screened, 45 were included, and 11 (24.4%) failed to be extubated. Mean MIP (23.5 ± 11.8 vs. 32.4 ± 9.3, p = 0.134) and RSBI (57.2 ± 26.5 vs. 55.3 ± 20.4, p = 0.803) were not different between the two groups. The proportions of patients whose MIP or RSBI satisfied the cutoff for extubation were not different between the groups. There were no significant differences in age, sex, body mass index, comorbidities, nutritional status, and cause of intubation between the two groups. The extubation failure group showed a higher proportion of decreased skeletal muscle mass (90.9% vs. 58.8%, p = 0.05) and longer duration of MV (10.7 ± 4.1 vs. 9.6 ± 3.4, p < 0.001) than the extubation success group. Multivariate analysis showed that the duration of intubation (OR = 1.439, 95% CI = 1.12–1.85), and decreased skeletal muscle mass (OR = 24.382, 95% CI = 1.00–594.86) were associated with extubation failure. Conclusions: Decreased skeletal muscle mass was associated with extubation failure after long-term MV for > 7 days. It is important to diagnose decreased skeletal muscle mass in critically ill patients to reduce extubation failure rates.